2022
DOI: 10.1111/obr.13539
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids, stress and eating: The mediating role of appetite‐regulating hormones

Abstract: Disrupted hormonal appetite signaling plays a crucial role in obesity as it may lead to uncontrolled reward-related eating. Such disturbances can be induced not only by weight gain itself but also by glucocorticoid overexposure, for example, due to chronic stress, disease, or medication use. However, the exact pathways are just starting to be understood. Here, we present a conceptual framework of how glucocorticoid excess may impair hormonal appetite signaling and, consequently, eating control in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 219 publications
(419 reference statements)
0
12
0
Order By: Relevance
“…We propose 2 theories to explain this situation: one is the effect of dexamethasone on the kidneys, which increases the glomerular filtration rate, antagonizing the effect of HCT [ 22 ], and the other is that dexamethasone can lead to improvement in appetite signaling [ 23 ] but it was misunderstood in our patient with the increase in drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…We propose 2 theories to explain this situation: one is the effect of dexamethasone on the kidneys, which increases the glomerular filtration rate, antagonizing the effect of HCT [ 22 ], and the other is that dexamethasone can lead to improvement in appetite signaling [ 23 ] but it was misunderstood in our patient with the increase in drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…56 In a recent populationbased cohort study from the UK, weight gain of over 10% of body weight was observed in 10.2% of subjects who were chronically exposed to systemic glucocorticoids: women, younger people, those living in greater socioeconomic deprivation, and people who smoke were at higher risk. 57 Such weight gain is thought to be mediated by increased appetite 58,59 and reduced thermogenesis (via suppressing the function of brown adipose tissue). [60][61][62][63]…”
Section: Therapies For Asthma and Allergic And Autoimmune/inflammator...mentioning
confidence: 99%
“…[ 5 ] Further more, studies suggest potential antidepressant effects of GLP-1RAs, [ 6 8 ] which may be related to their involvement in the regulation of inflammation [ 9 , 10 ] and hormones such as cortisol and thyroid hormones. [ 11 ] Here, we report a case of a young male who developed depressive symptoms after using Liraglutide for blood sugar control and weight reduction. This patient, a young male with no history of depression, experienced worsening depressive symptoms after increasing the dose of Liraglutide.…”
Section: Introductionmentioning
confidence: 99%